Seroprevalence of 2009 H1N1 Virus Infection and Self-Reported Infection Control Practices Among Healthcare Professionals Following the First Outbreak in Bangkok, Thailand - Kulkanya Chokephaibulkit (2018)
A serologic study with simultaneous self-administered questionnaire regarding infection control (IC) practices and other risks of influenza A (H1N1) pdm09 (2009 H1N1) infection was performed approximately 1month after the first outbreak among frontline healthcare professionals (HCPs). Of 256 HCPs, 33 (13%) were infected. Self-reported adherence to IC practices in >90% of exposure events was 82·1%, 73·8%, and 53·5% for use of hand hygiene, masks, and gloves, respectively. Visiting crowded public places during the outbreak was associated with acquiring infection (OR 3·1, P=0·019). Amongst nurses, exposure to HCPs with influenza-like illness during the outbreak without wearing a mask was the only identified risk factor for infection (OR=2·3, P=0·039). © 2012 Blackwell Publishing Ltd.